Comparison of Lactase Variant MCM6 -13910 C>T Testing and Self-report of Dairy Sensitivity in Patients With Irritable Bowel Syndrome. Issue 6 (July 2019) - Almazar, Ann E.; Chang, Joseph Y.; Larson, Joseph J.; Atkinson, Elizabeth J.; Locke, G. Richard; Talley, Nicholas J.; Saito, Yuri A.
Abstract : Goals: To evaluate agreement of MCM6 -13910 with self-report of dairy sensitivity (DS) and lactose hydrogen methane breath test (LHMBT) results in subjects with irritable bowel syndrome (IBS). Background: IBS is a functional gastrointestinal disorder with symptoms including abdominal pain, variable bowel habits, and bloating. Adult patients with lactose malabsorption may present with similar symptoms. Patients with lactose malabsorption have a lactase nonpersistent (LNP) phenotype. Recent studies found 2 single nucleotide polymorphisms associated with LNP: G/A-22018 and C/T-13910 . Study: Genotyping the MCM6 -13910 variant of LNP in 538 IBS patients and 317 controls (without IBS). Subjects completed questionnaires pertaining to gastrointestinal problems and dietary consumption, with charts abstracted. Results: Self-reported DS was higher in IBS (45%) than controls (9.8%, odds ratio=6.46, P <0.001). The C/C-13910 genotype was similar in IBS cases and controls, 81 (15.1%) and 47 (14.8%). Among subjects reporting DS, 49 (18.0%) had the C/C genotype. Overall agreement between genotype and self-reported DS was 0.06 in IBS and 0.07 in controls. There were 20 subjects with LHMBT results; 3 had positive results, 17 were negative. LNP genotypes were found in all 3 of positive LHMBT results; 16 had negative LHMBT among the 17 who were lactase persistent. Agreement between C/C-13910 genotype and LHMBT was excellent with κ-statistic of 0.83 (0.50-1.00). Conclusions: In IBS patients, self-report of lactose intolerance are highly prevalent but are a poor indicator of underlying C/C-13910 genotype. LHMBT had excellent agreement with C/C-13910 genotype.